Recurrent jaundice caused by recurrent hyperemesis gravidarum. Issue 12 (December 1984) - Larrey, D; Rueff, B; Feldmann, G; Degott, C; Danan, G; Benhamou, J P
Abstract : The existence of jaundice induced by hyperemesis gravidarum is controversial. We report the case of a woman who suffered from three episodes of jaundice during the first trimester of three consecutive pregnancies, a few days after the onset of hyperemesis gravidarum. Jaundice was caused by conjugated hyperbilirubinaemia. Serum alanine aminotransferase activity was increased and scarce necrotic hepatocytes were shown on light and electron microscopic examinations. Cessation of vomiting was rapidly followed by complete recovery. This observation supports the view that severe vomiting can cause jaundice in pregnant women.